2021
DOI: 10.1001/jamanetworkopen.2021.19769
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Implementation of Multiple Enhanced Recovery After Surgery Pathways Across a Provincial Health Care System in Alberta, Canada

Abstract: IMPORTANCE Engaging multidisciplinary care teams in surgical practice is important for the improvement of surgical outcomes. OBJECTIVE To evaluate the association of multiple Enhanced Recovery After Surgery (ERAS) pathways with ERAS guideline adherence and outcomes. DESIGN, SETTING, AND PARTICIPANTS This quality improvement study compared a pre-ERAS cohort (2013-2017) with a post-ERAS cohort (2014-2018). All patients were from Alberta Health Services in Alberta, Canada, and had available ERAS and up to 1-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…FTS focuses on a multidisciplinary approach to problem solving and decision making through the implementation of an integrated medical and nursing approach, which brings together the strengths of each field and integrates them with a common goal, so that an integrated medical and nursing approach to rapid perioperative rehabilitation interventions is necessary to enable patients to recover after surgery (10,11). Domestic and international studies (12,13) have reported that integrated medical and nursing rehabilitation interventions based on the FTS concept have been used in thoracic surgery, spine surgery, orthopedics, and cancer patients with more extensive results making them safe, effective, and improving their prognosis. However, in China, reports on the application of integrated medical and nursing perioperative rehabilitation interventions under the FTS concept in the perioperative period of TBI are rare.…”
Section: Discussionmentioning
confidence: 99%
“…FTS focuses on a multidisciplinary approach to problem solving and decision making through the implementation of an integrated medical and nursing approach, which brings together the strengths of each field and integrates them with a common goal, so that an integrated medical and nursing approach to rapid perioperative rehabilitation interventions is necessary to enable patients to recover after surgery (10,11). Domestic and international studies (12,13) have reported that integrated medical and nursing rehabilitation interventions based on the FTS concept have been used in thoracic surgery, spine surgery, orthopedics, and cancer patients with more extensive results making them safe, effective, and improving their prognosis. However, in China, reports on the application of integrated medical and nursing perioperative rehabilitation interventions under the FTS concept in the perioperative period of TBI are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Sutures were tied without strangulation of tissue but ensured the tip of the surgeon's fifth digit could not pass the fascia. Perioperative care was as per the Enhanced Recovery After Surgery protocols at our institution (15,16). This includes preoperative administration of 1000mg acetaminophen and 400mg ibuprofen 1-hour prior to surgery, as well as scheduled acetaminophen and non-steroidal anti-inflammatory administration post-operatively unless allergies or contraindications exist.…”
Section: Methodsmentioning
confidence: 99%
“…28 Although the evidence of benefit is clear, GIRFT has observed reduced emphasis on delivery and development of ER pathways. 29,30 Additionally, there is unwarranted variation across surgical sub-specialties in enrolment to ER programmes, despite a high number of commonalities in pathways between specialties. 5 A simplified and generic enhanced recovery concept has been developed to improve early postoperative recovery by focusing on early drinking, eating, and mobilising (DREAMing).…”
Section: The Elective Surgical Populationmentioning
confidence: 99%